2018
DOI: 10.1590/1807-1929/agriambi.v22n4p231-236
|View full text |Cite
|
Sign up to set email alerts
|

Gas exchange and organic solutes in forage sorghum genotypes grown under different salinity levels

Abstract: A B S T R A C TAdaptation of plants to saline environments depends on the activation of mechanisms that minimize the effects of excess ions on vital processes, such as photosynthesis. The objective of this study was to evaluate the leaf gas exchange, chlorophyll, and organic solute in ten genotypes of forage sorghum irrigated with solutions of different salinity levels. The experiment was conducted in a randomized block design, in a 10 x 6 factorial arrangement, with three replications, using ten genotypes -F3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
3
10
0
1
Order By: Relevance
“…Physiological disturbances in glycophytes caused by salt stress were verified by Cha-um and Kirdmanee (2011) and Freire et al (2014), corroborating the results observed in passion fruit plants irrigated with saline water. The use of saline water in Vigna unguiculata and Sorghum bicolor also reduced the photosynthetic rate, as observed in the present study, attributed to the partial closure of the stomata (NEVES et al, 2009;SILVA et al, 2013;COELHO et al, 2018). Prolonged exposure to salts causes changes in the stomatal conductance of the plant, thereby limiting the influx of CO 2 into the mesophyll.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Physiological disturbances in glycophytes caused by salt stress were verified by Cha-um and Kirdmanee (2011) and Freire et al (2014), corroborating the results observed in passion fruit plants irrigated with saline water. The use of saline water in Vigna unguiculata and Sorghum bicolor also reduced the photosynthetic rate, as observed in the present study, attributed to the partial closure of the stomata (NEVES et al, 2009;SILVA et al, 2013;COELHO et al, 2018). Prolonged exposure to salts causes changes in the stomatal conductance of the plant, thereby limiting the influx of CO 2 into the mesophyll.…”
Section: Resultssupporting
confidence: 75%
“…One of the effects of salt stress is the reduction in the availability of water to plants, which causes significant decreases in photosynthetic activity, transpiration and stomatal conductance, and this condition is mainly related to stomatal closure. Neves et al (2009) and Silva et al (2013), studying cowpea and Coelho et al (2018) studying sorghum, also found that salt stress negatively affected plant transpiration.…”
Section: Resultsmentioning
confidence: 98%
“…Reductions in gas exchange of plants subjected to saline environments are associated with the osmotic effect on plant metabolism (Silva et al, 2013). Studies with fodder sorghum have shown that the continuous use of water with salinity above the threshold of the crop reduces the rate of transpiration due to partial closure of the stomata (Coelho et al, 2018). Liu et al (2015) reported a direct influence of salinity on the water and photosynthetic relationships of sorghum leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Its great genetic variability enables different responses when subjected to salt stress (Tabatabaei and Anagholi, 2012). These are reflected in physiological variables (stomatal conductance, transpiration rate and photosynthesis) (Freire et al, 2014), biometric variables (height, leaf area, biomass production) (Costa et al, 2019;Guimarães et al, 2019), and biochemical variables (osmoregulatory solutes, antioxidant enzymes) (Barbosa et al, 2014;Coelho et al, 2018).…”
Section: Sorghum (Sorghum Bicolor (L) Moench)mentioning
confidence: 99%